Electrical conductivity and ferroelastic properties of Ti-substituted solid solutions (1 − x) BiFeO3 – x Bi0.5K0.5TiO3. Issue 3 (February 2016) - Wefring, Espen Tjønneland; Schader, Florian H.; Webber, Kyle G.; Einarsrud, Mari-Ann; Grande, Tor
Abstract: The high crystallographic strain and polarization of BiFeO3 are attractive, but utilization of bulk BiFeO3 has been hindered by large leakage current and high coercive field. Here, we report on the electrical conductivity and ferroelasticity of BiFeO3 substituted with 10 and 20 mol% Bi0.5 K0.5 TiO3 . The electrical conductivity is reduced by several orders of magnitude with donor substitution of Fe with Ti, which also suppressed the strong dependence of the conductivity on partial pressure of oxygen. Hard ferroelastic properties of the as-sintered materials were demonstrated by stress–strain measurements. The coercive stress was strongly reduced by quenching from above the ferroelectric to paraelectric phase transition, and the remanent strain increased and coercive stress decreased with increasing temperature up to 400 °C. Ferroelastic hardening was also observed with increasing Ti-donor substitution. The effect of donor substitution is discussed with respect to point defect chemistry and possible hardening mechanisms related to point defects.